Rancang Bangun Trainer Motor Bensin Empat Langkah - Muhammad Ginanjar Wisnu Kawiryan, Agung Samudra (Universitas Hasyim Asy'ari, 2021)
Trainer is a tool used to support learning activities, training, and introduction of materials in education. In general, trainers or props are widely used in the world of education, namely to support educational methods that use methods of application of theory by means of practice or trials. Where it is necessary to make a 4-step gasoline motor trainer with the aim as a means of practice and to analyze the work process and function of a 4-step gasoline motor. Research design 4-step gasoline motor trainers using development methods (researtch and development). While the analysis of trainer testing uses descriptive methods. In the trainer design process is started with the frame design process, cutting the materials used, welding process, smoothing process, and painting process and the last is the process of assembling all trainer components. The results obtained in the implementation of research and testing resulted in a tool in the form of a 4-step gasoline motor trainer made from galvalume 4x4 iron, and a 4-step gasoline motor type MCN 110cc. While the process of analysis of the results of 4-step gasoline motor trainer testing is obtained with the results of all component mechanisms, including valve mechanisms, transmission mechanisms, and clutch mechanisms can work properly and normally according to initial planning.